(untitled) (Eureka Journal of Civil, Architecture and Urban Studies, 2026)
This paper investigates the influence of technological factors on the tribological behavior of metal matrix nanocomposites. The study focuses on the relationship between fabrication technology, thermomechanical conditions, and friction and wear processes occurring during sliding contact. Experimental tribological tests demonstrate that nanophase-reinforced metal matrix composites exhibit significantly lower friction coefficients and wear rates compared to the base metal. An increase in nanophase content leads to improved friction stability and promotes the formation of protective tribological layers on the contact surface. Microstructural observations reveal a reduction in the thickness of the plastically deformed surface layer and a limitation of deformation propagation into the bulk material. The results indicate that the tribological performance of metal matrix nanocomposites is governed not only by material composition but also by processing conditions and surface evolution during friction. These findings provide a scientific basis for the design of wear-resistant materials for tribologically demanding applications.